An Evaluation of School Operational Fund Program - Son Haji; Bukman Lian; Yessi Fitriani (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2020)
This study aimed at determining the planning and accountability as well as the benefits and impacts of the BOS funding program in SD Negeri 01 Pulau Rimau, Banyuasin. The data sources of this research were the principal, teachers and students of SD Negeri 01 Pulau Rimau. The method used qualitative and applied interviews, documentation and observation as instruments. The results showed that 1) BOS program planning was realized in the RAPBS; 2) the use of BOS funds has been carried out in accordance with the 2015 National Technical Guidelines used by schools; 3) accountability of BOS funds in the form of memorandum of purchase and maintenance of equipment as well as for payment of teacher honoraria at schools; 4) and the benefits and impacts of the BOS program for schools is that the learning process runs effectively by always improving the quality of facilities.